(untitled) (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
This paper explores the multifaceted issues surrounding cell phone theft and the illicit manipulation of International Mobile Equipment Identity numbers, which serve as unique identifiers for mobile devices. The International Mobile Equipment Identifier is a critical component for identifying mobile devices globally, akin to a serial number, and is factory-assigned, stored in the device’s firmware, and transmitted during network authorization. Despite its intended permanence, the IMEI can be illegally altered or cloned, facilitating the resale of stolen devices and complicating efforts to track and recover them. This paper delves into the technological vulnerabilities that enable such manipulation, the sophisticated methods employed by perpetrators, and the consequential challenges faced by law enforcement and network providers in combating this evolving threat. Furthermore, it examines the current strategies for detection and prevention, including the role of centralized databases like the Central Equipment Identity Register in blacklisting stolen devices and the continuous efforts by manufacturers to enhance tamper-proof IMEI storage. The discussion extends to an analysis of the legal frameworks and international collaborations aimed at mitigating the impact of cell phone theft and IMEI manipulation, offering insights into policy gaps and potential areas for reform.